Ion Transfer Voltammetry at Thin Films Based on Functionalized Cationic [6]Helicenes. Issue 4 (5th December 2017) - Jarolímová, Zdeňka; Bosson, Johann; Labrador, Geraldine M.; Lacour, Jérôme; Bakker, Eric
Abstract: We describe a new family of molecular ion‐to‐electron redox probes based on cationic diaza, azaoxa, and dioxa [6]helicenes and their derivatives. Their unique structure combines, in a single framework, two privileged families of molecules – helicenes and triaryl methyl carbenium moieties. These cationic [6]helicenes exhibit reversible and reproducible oxidation/reduction behavior and facilitate the ion transfer into thin layer sensing films composed of bis(2‐ethylhexyl)sebacate (DOS), polyurethane (PU), sodium tetrakis 3.5‐bis(trifluoromethyl)phenyl borate, sodium ionophore X and diaza + (C8 )2 Br2 for cation transfer. Cyclic voltammetry is used to interrogate the thin films. The cationic response can be tuned by adjusting the membrane loading. Addition of lipophilic cation exchanger into the membrane film results in transfer waves of Gaussian shape for cations. A peak separation of 60 mV and peak width of 110 mV are near the theoretical values for a surface confined process. While Nernstian shifts of the peak potentials with analyte concentration is obtained for membranes based on cationic [6]helicenes and doped with sodium‐selective ionophore X, this ionophore was found to promote a gradual loss of redox active species from the ionophore‐based membranes into the sample solution. Abstract :